2021
DOI: 10.2196/25636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vaccine Tweets During the Early Stage of the COVID-19 Outbreak in the United States: Topic Modeling Analysis

Abstract: Background During the early stages of the COVID-19 pandemic, developing safe and effective coronavirus vaccines was considered critical to arresting the spread of the disease. News and social media discussions have extensively covered the issue of coronavirus vaccines, with a mixture of vaccine advocacies, concerns, and oppositions. Objective This study aimed to uncover the emerging themes in Twitter users’ perceptions and attitudes toward vaccines duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…For example, some studies [22][23][24][25][26] collected tweets over the course of the COVID-19 pandemic to examine public sentiments and opinions regarding COVID-19 vaccines. Researchers [27,28] conducted topic modeling and emotion analyses to identify the themes and emotions related to the COVID-19 vaccines to aid public health officials in the battle against COVID-19.…”
Section: Social Media For Public Health Researchmentioning
confidence: 99%
“…For example, some studies [22][23][24][25][26] collected tweets over the course of the COVID-19 pandemic to examine public sentiments and opinions regarding COVID-19 vaccines. Researchers [27,28] conducted topic modeling and emotion analyses to identify the themes and emotions related to the COVID-19 vaccines to aid public health officials in the battle against COVID-19.…”
Section: Social Media For Public Health Researchmentioning
confidence: 99%
“…The most commonly derived main topic was the concern about AEs, which was the main topic reported in 6 studies [ 4 , 6 , 10 - 13 ]. Previous topic modeling studies have shown that vaccine efficacy [ 8 , 11 , 17 , 18 ] and hesitancy [ 4 , 5 , 19 ] are the most common topics. Vaccine development and progress were the second-most discussed topics, discussed in 5 studies [ 8 , 11 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous topic modeling studies have shown that vaccine efficacy [ 8 , 11 , 17 , 18 ] and hesitancy [ 4 , 5 , 19 ] are the most common topics. Vaccine development and progress were the second-most discussed topics, discussed in 5 studies [ 8 , 11 , 18 , 20 , 21 ]. Certain people, such as Bill Gates and Kamala Harris, were mentioned as topic words [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective observational event-driven infoveillance study, we sought to characterize public user reaction to the death of Hank Aaron on Twitter for purposes of expanding the literature on minority-specific COVID-19 misinformation topics as detected on social media platforms. Twitter was chosen for this study because previous research has shown that misinformation, and specifically vaccine-related misinformation and disinformation (including general antivaccination topics, misinformation about non-COVID-19 vaccines, and misinformation specific to COVID-19 vaccines), is prominent on the platform [3][4][5][6][7][8]. Additionally, information and news reports about both Aaron's initial vaccination and his death were shared on Twitter making it an ideal platform to further explore user interaction, sentiment, and dissemination of this content.…”
Section: Introductionmentioning
confidence: 99%